2009
DOI: 10.1007/s00125-009-1628-9
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of depression but not anxiety are associated with central obesity and cardiovascular disease in people with type 2 diabetes: the Edinburgh Type 2 Diabetes Study

Abstract: Aims/hypothesis The aim of the study was to identify risk factors for depression and anxiety in a well-characterised cohort of individuals with type 2 diabetes mellitus. Methods We used baseline data from participants (n=1,066, 48.7% women, aged 67.9±4.2 years) from the Edinburgh Type 2 Diabetes Study. Symptoms of anxiety and depression were assessed using the Hospital Anxiety and Depression Scale (HADS). Obesity was characterised according to both overall (body mass index, fat mass) and abdominal (waist circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 10 publications
1
33
0
1
Order By: Relevance
“…Also, in spontaneously diabetic INS2 Akita mouse, Asakawa and colleagues reported anxiety-like behavior using the elevated plus maze test [65]. Labad and colleagues recently have shown that depression but not anxiety is associated with type-2 diabetes [66]. Results of anxiety and depression screening of db/db mice are consistent with this clinical report showing the presence of depression but not anxiety.…”
Section: Discussionsupporting
confidence: 62%
“…Also, in spontaneously diabetic INS2 Akita mouse, Asakawa and colleagues reported anxiety-like behavior using the elevated plus maze test [65]. Labad and colleagues recently have shown that depression but not anxiety is associated with type-2 diabetes [66]. Results of anxiety and depression screening of db/db mice are consistent with this clinical report showing the presence of depression but not anxiety.…”
Section: Discussionsupporting
confidence: 62%
“…However, most of the studies have only evaluated indirect measurements of adiposity, such as BMI and WC [5-8]. These anthropometric variables, although largely used in clinical practice, may neither indicate the total body fat nor differentiate lean from fat mass.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, anxiety has been found to be associated with lifetime severe hypoglycemia, but not abdominal obesity or cardiovascular disease, in longitudinal analysis [38]. Overall, these recent studies continue to show a relationship between anxiety and diabetes, although the strength of the associations is weaker than those found for the association between diabetes and depression.…”
Section: Association Between Anxiety and Diabetes Outcomesmentioning
confidence: 95%